The Art of Eating: Nourishing Instincts and Balancing Intuitive Eating - Jańczyk, Natalia; Jankowska, Marlena; Baran, Karolina; Winkowska, Alicja; Mędrysa, Karolina; Pokrzepa, Jakub Jan; Presak, Michał; Blecharz, Gabriela; Szwech, Julia; Pograniczny, Mikołaj (Quality in Sport, 2025)
This dissertation explores the crucial role of nutrition in optimising athletic performance. It examines the interplay between foundational nutritional knowledge – as we know it in science – and the evolving trend of so-called intuitive eating. The fundamental importance of macronutrients (carbohydrates, proteins, and fats) and micronutrients for fuelling training, as well as promoting recovery and preventing injury, is discussed. The topic of controlling glucose spikes is briefly touched upon, and understanding the specific nutritional requirements of various sports is emphasised. The dissertation synthesises knowledge of principles, benefits and potential challenges of intuitive eating with athletes’ needs. Ultimately, this work highlights a holistic approach, amalgamating both what the scientific world has to offer and the individualistic liberation that intuitive eating has to offer for achieving peak athletic performance and psychological well-being.